Non-stick "green" cookware: Does it measure up to manufacturers' claims? / Charles C. Broz ... [et al.] - Broz, Charles C.; Taylor, D. Christopher; Barr, Jonathan (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2015)
For the past decade, there has been much controversy over the dangers of non-stick polytetrafluoroethylene (PTFE) coated cookware. In response to the demand for a new non-stick product, manufacturers have developed environmentally friendly, non-PTFE alternatives. These "green" pans are supposedly non-stick and exceptionally durable. However, laboratory testing of these pans, as well as customer reviews, suggests a lack of credibility to such claims. This experiment was conducted to replicate television cooking demonstrations for non-stick cookware. A durability test was also conducted to assess the hardness of the ceramic coating.